Quadruplex DNA in long terminal repeats in maize LTR retrotransposons inhibits the expression of a reporter gene in yeast - Viktor Tokan; Janka Puterova; Matej Lexa; Eduard Kejnovsky (BMC Genomics, 2018)
Abstract Background Many studies have shown that guanine-rich DNA sequences form quadruplex structures (G4) in vitro but there is scarce evidence of guanine quadruplexes in vivo. The majority of potential quadruplex-forming sequences (PQS) are located in transposable elements (TEs), especially close to promoters within long terminal repeats of plant LTR retrotransposons. Results In order to test the potential effect of G4s on retrotransposon expression, we cloned the long terminal repeats of selected maize LTR retrotransposons upstream of the lacZ reporter gene and measured its transcription and translation in yeast. We found that G4s had an inhibitory effect on translation in vivo since “mutants” (where guanines were replaced by adenines in PQS) showed higher expression levels than wild-types. In parallel, we confirmed by circular dichroism measurements that the selected sequences can indeed adopt G4 conformation in vitro. Analysis of RNA-Seq of polyA RNA in maize seedlings grown in the presence of a G4-stabilizing ligand (NMM) showed both inhibitory as well as stimulatory effects on the transcription of LTR retrotransposons. Conclusions Our results demonstrate that quadruplex DNA located within long terminal repeats of LTR retrotransposons can be formed in vivo and that it plays a regulatory role in the LTR retrotransposon life-cycle, thus also affecting genome dynamics.